Magnetisation transfer imaging biomarkers of demyelination in multiple sclerosis - York, Elizabeth N. (The University of Edinburgh, 2022)
Multiple sclerosis (MS) is an immune-mediated, neurodegenerative disease of the central nervous system (CNS) characterised by focal demyelination (lesions) and axonal loss. Clinical presentation is heterogeneous; yet the relapsing-remitting MS (RRMS) sub-type is defined by acute clinical episodes, which distinguish it from continuously worsening disability in progressive sub-types. Early intervention with disease modifying therapies (DMTs) may prevent neurodegeneration. Current DMTs, however, generally target inflammation, are expensive and are limited by accompanying adverse effects. In vivo biomarkers are thus warranted for early stratification of patients, longitudinal observation of therapeutic response and evaluation of novel treatments. Magnetic resonance imaging (MRI) plays a key role in MS diagnosis; yet the predictive power of conventional MRI biomarkers, such as T2-w lesion load and brain atrophy, to determine prognosis and disease severity in early disease is weak. Advanced MRI techniques such as magnetisation transfer imaging (MTI) and diffusion-weighted imaging (dMRI), which probe tissue microstructure non-invasively, may be more sensitive to MS neuropathology, and show promise as putative biomarkers of underlying MS pathology. Quantitative MTI has been widely applied in MS studies. Poor intra- and inter-site reproducibility of the derived magnetisation transfer ratio (MTR) metric and the time-consuming protocols required for fully quantitative MTI have restricted clinical usage of MTI. MTsat, a semi-quantitative MTI measure, is less influenced by variance in the MTR signal caused by T1 relaxation and B1 inhomogeneities, and thus may be a better prognostic biomarker than MTR. Combining quantitative MTI with dMRI measures may also improve specificity to the heterogeneous biological processes which occur in MS at diagnosis. In this work, I assessed MTI literature in RRMS through systematic review and meta-analyses. I compared the reproducibility of MTsat with MTR in healthy volunteers. I also assessed the reproducibility of the MRI aggregate g-ratio, derived from combined MTsat and dMRI-derived neurite orientation dispersion and density imaging (NODDI) measures. I validated the use of MTsat in a clinical cohort of people recently diagnosed with RRMS, before therapeutic intervention, and evaluated the relationship between MTI biomarkers and clinical disability. We substantiate the MRI g-ratio as a biomarker in RRMS by comparing it with an established blood biomarker of axonal damage, neurofilament. Finally, I determine the longitudinal evolution of MTsat, compared with MTR, and g-ratio in early RRMS.
Keywords: MRI; multiple sclerosis; magnetisation transfer; myelin; g-ratio; diffusion; magnetisation transfer saturation; quantitative MRI; relapsing-remitting multiple sclerosis